Political comunication trends in the digital age in Ecuador - Zuñiga Oñate, Joselyn Michelle (Scripta Mundi, 2022)
In this research, the issue of political communication in the digital age in Ecuador is addressed, since digital technologies have transformed political communication in the country. The methodology used was the bibliographic and documentary review, which allowed to examine the online political communication practices of the main political actors of the country, political parties and citizens. Among the results, it is highlighted that the use of social networks has had a significant impact, which leads to an increase in citizen interaction and participation in political processes, and greater dissemination in their messages. However, the need for adequate regulation to prevent the spread of false information and the manipulation of public opinion has also become evident. It is necessary to understand the impact of political communication on democracy and the need to encourage informed and critical citizen participation.